(untitled) (Research, Society and Development, 2021)
The search for quality has become constant in several areas, including customer service, as it is an opportunity that the company has to achieve customer satisfaction and retention, also, through a lasting relationship with customers. The objective of the research is to analyze the quality of the service and its influences on the relationship with the customer in the clothing and accessories sector. The research methodology is classified as descriptive, quantitative with the use of a closed questionnaire applied to 219 clients, and qualitative with the use of an interview script. The results showed that the results of the research demonstrate that the quality of the service did not influence the relationship with the company’s client. It was conclusive that the quality of the service has not influenced the Relationship with the Customers of the Clothing Store in the State of Tocantins and accessories, as the company’s service was evaluated in a positive way, framing in a quality service.